2019
DOI: 10.3389/fonc.2019.01091
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Roles of Non-coding RNAs in Angiogenesis and Neovascularization From an Epigenetic Perspective

Abstract: Angiogenesis is a crucial process for organ morphogenesis and growth during development, and it is especially relevant during the repair of wounded tissue in adults. It is coordinated by an equilibrium of pro- and anti-angiogenic factors; nevertheless, when affected, it promotes several diseases. Lately, a growing body of evidence is indicating that non-coding RNAs (ncRNAs), such as miRNAs, circRNAs, and lncRNAs, play critical roles in angiogenesis. These ncRNAs can act in cis or trans and alter gene transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 169 publications
(132 reference statements)
0
20
0
1
Order By: Relevance
“…They can regulate cancer cell proliferation, migration, and invasion [6]. Also circRNAs can contribute to cancer development through the regulation of angiogenesis and neovascularization [34]. For instance, circRNA MYLK promotes bladder cancer progression and metastasis via enhancing cancer cell growth and angiogenesis [35].…”
Section: Discussionmentioning
confidence: 99%
“…They can regulate cancer cell proliferation, migration, and invasion [6]. Also circRNAs can contribute to cancer development through the regulation of angiogenesis and neovascularization [34]. For instance, circRNA MYLK promotes bladder cancer progression and metastasis via enhancing cancer cell growth and angiogenesis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that miRNAs play a critical role in angiogenic processes [ 160 ]. In particular, miR-424 is expressed in a sequential manner during the endothelial differentiation of DPSCs.…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“… 161 , 162 Furthermore, various miRNAs mediate the expression of epigenetic elements, such as DNMTs (regulated by miR-152, miR-30, and miR-148a/b), HDACs (regulated by miR-140, miR-1, and miR-449a), and a polycomb group of genes (regulated by miR-101 and miR-26a). 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 Previous studies have indicated that miRNAs are expressed in the vascular system. As shown in Table 1 , numerous studies have indicated that miRNAs impinge on a wide variety of cellular activity networks, related to the ISR biological pathway, including VSMC and EC function.…”
Section: Main Textmentioning
confidence: 99%